Beginning HTML5 and CSS3 - Clark, Richard; Studholme, Oli.; Murphy, Christopher; Manian, Divya; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2012)
Beginning HTML5 and CSS3 is your introduction to the new features and elements of HTML5$1 (Bas a web developer you'll learn about all the leaner, cleaner, and more efficient code available now with HTML5, along with some new tools that will allow you to create more meaningful and richer content. For everyone involved in web design, this book also introduces the new structural integrity and styling flexibility of CSS 3$1 (Bwhich means better-looking pages and smarter content in your website projects. For all forward-looking web professionals who want to start enjoying and deploying the new HTML5 and CSS3 features right away, this book provides you with an in-depth look at the new capabilities$1 (Bincluding audio and video$1 (Bthat are new to web standards. You$1 (Bll learn about the new HTML5 structural sections, plus HTML5 and CSS3 layouts. You$1 (Bll also discover why some people think HTML5 is going to be a Flash killer, when you see how to create transitions and animations with these new technologies. So get ahead in your web development through the practical, step-by-step approaches offered to you in Beginning HTML5 and CSS3.s
Keywords: Computer science; Computer Science; Computer Science, general